Bile Acids Gate Dopamine Transporter Mediated Currents - Romanazzi, Tiziana; Zanella, Daniele; Cheng, Mary Hongying; Smith, Behrgen; Carter, Angela M.; Galli, Aurelio; Bahar, Ivet; Bossi, Elena (Frontiers in Chemistry, 2021)
Bile acids (BAs) are molecules derived from cholesterol that are involved in dietary fat absorption. New evidence supports an additional role for BAs as regulators of brain function. Interestingly, sterols such as cholesterol interact with monoamine transporters (MAT), including the dopamine (DA) transporter (DAT) which plays a key role in DA neurotransmission and reward circuitries in the brain. The present study explores interactions of the BA, obeticholic acid (OCA), with DAT and mechanistically defines the regulation of DAT activity via both electrophysiology and molecular modeling. We express murine DAT (mDAT) in Xenopus laevis oocytes and confirm that DA induces an inward current that reaches a steady-state at a negative membrane voltage. Next, we show that OCA triggers an inward current through DAT that is Na+ dependent and not regulated by intracellular calcium. OCA also inhibits the DAT-mediated Li+ leak current, a feature that parallels DA action and indicates direct binding to the transporter. Interestingly, OCA does not alter DA affinity nor the ability of DA to promote a DAT-mediated inward current, suggesting that the interaction of OCA with the transporter is non-competitive, in regard to DA. The current induced by OCA is transient in nature, returning to baseline in the continued presence of the BA. To understand the molecular mechanism of how OCA affects DAT electrical activity, we performed docking simulations. These simulations revealed two potential binding sites that provide important insights into the potential functional relevance of the OCA-DAT interaction. First, in the absence of DA, OCA binds DAT through interactions with D421, a residue normally involved in coordinating the binding of the Na+ ion to the Na2 binding site (Borre et al., 2014;Cheng and Bahar, 2015). Furthermore, we uncover a separate binding site for OCA on DAT, of equal potential functional impact, that is facilitated through the residues DAT R445 and D436. This binding may stabilize the inward-facing open (IFo) state by preventing the re-formation of the IF gating salt bridges, R60-D436 and R445-E428, that are required for DA transport. This study suggests that BAs may represent novel pharmacological tools to regulate DAT function, and possibly, associated behaviors.